Perancangan Sistem Pakar Diagnosa Kerusakan Pada Kamera DSLR Canon Dengan Metode Forward Chaining Berbasis Web - Danangda Rizky Ramadhan; Hadion Wijoyo (Mahesa Research Institute, 2021)
At present the use of camera technology has grown rapidly with the emergence of various types of cameras with various advantages, such as cameras with the Canon DSLR type. Most people use it not only for hobbies, but also for work. With the development of Artificial Intelligence technology, it allows Expert Systems to be applied to a network that can be accessed either via a computer device or a Smartphone device. One of them is in providing information about various problems that often occur with camera devices, especially hardware problems. The method used in this expert system is Forward Chainning, supported by supporting data. With the features provided for users and administrators, it is possible for both users and administrators to use this system according to their individual needs. Users are given an easy way to find information about various kinds of camera damage and symptoms that usually arise, by answering some of the questions the system gives. Meanwhile, administrators can be able to perform system management, both the process of adding, deleting, and updating the latest data. This final project is expected to be able to provide all information related to the problem of damage to Canon DSLR cameras for the general public, as well as photographers or videographers. Keywords: Expert System, Forward Chainning, DSLR Camera